Mahesh Dattani’s "Final Solutions": Role of Prejudice and Personal Enmity in communal violence. - Mr. Sumit (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2023)
The play "Final Solutions" by Mahesh Dattani depicts the deep-seated prejudice and enmity between the Hindu and Muslim communities in India, which leads to violent clashes between them. The play explores the relationships and prejudices that exist between the two communities, as well as the personal histories and grudges that fuel their hatred towards one another. This research paper examines the role of prejudice and personal enmity in the communal violence depicted in the play. The paper analyses the historical context of the play, which is set in the aftermath of the 1992 Babri Masjid demolition and the 2002 Gujarat riots. The paper then examines the characters in the play and their attitudes towards Muslims, highlighting the deep-rooted prejudices that underlie the violence between the two communities. The paper also examines the role of personal enmity in the communal violence depicted in the play.